Elevated blood pressure is not associated with accelerated glomerular filtration rate decline in the general non-diabetic middle-aged population - Eriksen, Bjørn Odvar; Stefansson, Vidar Tor Nyborg; Jenssen, Trond Geir; Mathisen, Ulla Dorte; Schei, Jørgen; Solbu, Marit Dahl; Wilsgaard, Tom; Melsom, Toralf (Kidney International, 2016)
Manuscript version. Published version at http://dx.doi.org/10.1016/j.kint.2016.03.021 Although hypertension is a risk factor for end-stage renal disease, this complication develops in only a minority of hypertensive patients. Whether non-malignant hypertension itself is sufficient to cause reduced glomerular filtration rate (GFR) is unclear. We investigated whether elevated blood pressure (BP) was associated with accelerated GFR decline in the general population. The study was based on the Renal Iohexol-clearance Survey in Tromsø 6 (RENIS-T6), which included a representative sample of 1594 subjects aged 50 to 62 years from the general population without baseline diabetes, kidney or cardiovascular disease. GFR was measured as iohexol clearance at baseline and follow-up after a median observation time of 5.6 years. BP was measured according to a standardized procedure. The mean (standard deviation) GFR decline rate was 0.95 (2.23) mL/min/year. In multivariable adjusted linear mixed regressions with either baseline systolic or diastolic BP as the independent variable, there were no statistically significant associations with GFR decline. We conclude that elevated BP is not associated with accelerated mean GFR decline in the general middle-aged population. Additional genetic and environmental factors are probably necessary for elevated BP to develop manifest chronic kidney disease in some individuals.